Pengabdian Kepada Masyarakat; Pengenalan & Pelatihan Aplikasi CANVA untuk Media Presentasi Pembelajaran di SDN 32 Mataram - Zinnurain Zinnurain; Mujiburrahman Mujiburrahman; Restu Wibawa (Jurnal Dedikasi Madani, 2024)
This activity aims to introduce and to train teachers at SDN 32 Mataram about the CANVA application for designing learning media as presentation media. This activity was carried out for 2 weeks starting from 27 May – 06 June 2024, taked time in the even semester of the 2023/2024 academic year. This Community Service activity used discussion and practicum methods. The instrument used to measure the success and achievement of this activity was a training questionnaire given before and after the training to the 8 teacher participants. The results of the activities showed that at stage-1 the evaluation results showed an increase in understanding based on the results of the questionnaires filled out, as many as 2 teachers understood the material presented and successfully completed the activities given by the team but in the "Low" category. In stage 2, the evaluation results showed an increase in understanding based on the results of a questionnaire which was filled out by showing a presentation of the work results of 4 teachers who understood the material presented and successfully completed the activities given by the team in the "Medium" category. In stage-3 the evaluation results show an increase in understanding. Based on the results of the questionnaire filled out, as many as 8 teachers understood the material presented and successfully completed the activities given by the team in the "High" category. It can be concluded that Community Service; Introduction & Training on the CANVA Application for Learning Presentation Media at SDN 32 Mataram can be categorized as "Successful"